2010
DOI: 10.1002/bmb.20415
|View full text |Cite
|
Sign up to set email alerts
|

Calibrated peer review for computer‐assisted learning of biological research competencies

Abstract: Recently, both science and technology faculty have been recognizing biological research competencies that are valued but rarely assessed. Some of these valued learning outcomes include scientific methods and thinking, critical assessment of primary papers, quantitative reasoning, communication, and putting biological research into a historical and broader social context. This article presents examples of Calibrated Peer Review (CPR) assignments that illustrate a computer-assisted method to help students achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…Critical-thinking and scientific reasoning skills are core learning objectives of science education for all students, regardless of whether or not they intend to pursue a career in science or engineering. Consistent with the view of learning as construction of understanding and meaning ( National Research Council, 2000 ), the pedagogical practice of writing has been found to be effective not only in fostering the development of students’ conceptual and procedural knowledge ( Gerdeman et al , 2007 ) and communication skills ( Clase et al , 2010 ), but also scientific reasoning ( Reynolds et al , 2012 ) and critical-thinking skills ( Quitadamo and Kurtz, 2007 ).…”
Section: Introductionmentioning
confidence: 79%
“…Critical-thinking and scientific reasoning skills are core learning objectives of science education for all students, regardless of whether or not they intend to pursue a career in science or engineering. Consistent with the view of learning as construction of understanding and meaning ( National Research Council, 2000 ), the pedagogical practice of writing has been found to be effective not only in fostering the development of students’ conceptual and procedural knowledge ( Gerdeman et al , 2007 ) and communication skills ( Clase et al , 2010 ), but also scientific reasoning ( Reynolds et al , 2012 ) and critical-thinking skills ( Quitadamo and Kurtz, 2007 ).…”
Section: Introductionmentioning
confidence: 79%
“…, 2008; Gunersel and Simpson, 2009; Rourke et al. , 2008; Clase et al. , 2010), while others have reported no benefit from the program (Walvoord et al.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies focused on graph interpretation, the concepts and skills that they studied are integral to graph construction as well. Before constructing the graph, the graph constructor should have a clear purpose in mind, along with an adequate understanding of variables and graph types ( Berg and Smith, 1994 ; Friel and Bright, 1996 ; Clase et al. , 2010 ; Grunwald and Hartman, 2010 ; Angra and Gardner, 2016 ).…”
Section: Concepts and Skills Needed For Graphing And Areas Of Difficumentioning
confidence: 99%